2019
DOI: 10.3390/ma12244051
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy (PBMT) Applied in Bone Reconstructive Surgery Using Bovine Bone Grafts: A Systematic Review

Abstract: The use of low-level laser therapy (LLLT) with biomodulatory effects on biological tissues, currently called photobiomodulation therapy (PBMT), assists in healing and reduces inflammation. The application of biomaterials has emerged in bone reconstructive surgery, especially the use of bovine bone due to its biocompatibility. Due to the many benefits related to the use of PBMT and bovine bones, the aim of this research was to review the literature to verify the relationship between PBMT and the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 75 publications
(263 reference statements)
1
29
0
1
Order By: Relevance
“…The PBMT protocol used in the present experiment is due to previous studies (in vivo) on tissue regeneration [8,12,13,16], plus a literature review on the action of PBMT specifically on bone tissue, in which the length of 830 nm was cited as the most used (40.79%) and with positive effects in 98.68% [67]; in another review, satisfactory results were observed between the PBMT and xenograft in 17 of the 18 articles included [23]. The literature points to laser-modulated bone formation with increased bone growth factors in differentiated cells by stimulating matrix secretion, cell proliferation and reduced inflammation [65,68].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PBMT protocol used in the present experiment is due to previous studies (in vivo) on tissue regeneration [8,12,13,16], plus a literature review on the action of PBMT specifically on bone tissue, in which the length of 830 nm was cited as the most used (40.79%) and with positive effects in 98.68% [67]; in another review, satisfactory results were observed between the PBMT and xenograft in 17 of the 18 articles included [23]. The literature points to laser-modulated bone formation with increased bone growth factors in differentiated cells by stimulating matrix secretion, cell proliferation and reduced inflammation [65,68].…”
Section: Discussionmentioning
confidence: 99%
“…PBMT has been shown to be an ally in the process of bone reconstruction; however, the consensus about parameters for the purpose of bone regeneration is still uncertain in the literature, since studies show varieties of protocols, thus obtaining different results [23,74,75] such as differentiation, density and osteogenic proliferation [67,74,76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, alternative non-invasive methods have been used in tissue regeneration, such as the use of low-level laser therapy (LLLT), currently called photobiomodulation therapy (PBMT) [ 17 , 18 , 19 , 20 , 21 , 22 ]. In the bone repair process, this therapy is known to exert analgesic anti-inflammatory effects, in addition to accelerating the regeneration process by providing cell proliferation and differentiation [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many scientific reports about xenografts in the bone repair process, whose results evidence that it is a viable alternative to autologous grafts [10]. There is currently a social and commercial incentive for alcohol consumption worldwide, which may lead to a larger number of patients using ethyl derivatives in clinical practice.…”
Section: Introductionmentioning
confidence: 99%